Computational fluid dynamic simulation study on NACA 4412 airfoil with various angle of attacks - Abdul Mukhti, Muhammad Ammar Qayyum; Didane, Djamal Hissein; Ogab, Mohammed; Manshoor, Bukhari (FAZ Publishing, 2021)
The aerodynamic airfoil blades have a crucial influence on the wind turbine's aerodynamic efficiency. Selecting an appropriate airfoil section for the blade is essential. The angle of attack and its effect on lift and drag forces such as the high lift and low drag or vice versa are the critical parameters that decide the efficiency of the wind turbine system. By taking this as a motivation to the presented work, the NACA 4412 airfoil profile is considered to study the effect of angle of attack on wind turbine blade's aerodynamic performance. According to national advisory committee for aeronautics (NACA) standards, the airfoil geometry is generated through computational fluid dynamics. The Simulation and analysis are performed for different angles of attack ranging from 0° to 18° with an increment of 2° for low Reynolds number. In the present research, the aerodynamic results are assessed in terms of static pressure and velocity distributions alongside different angles of attack. In addition, coefficient of lift, coefficient of drag and lift/drag ratio are also calculated and plotted against different angles of attack. From the CFD analysis, it is concluded that as the angle of attack increases when the lift/drag ratio reduces. The NACA 4412 airfoil provides the highest performance at an angle of attack of 13.8°. However, other factors should also be considered when assessing the aerodynamic performance of NACA airfoils, such as blade backflow turbulence and blade forces.